การแปลงตัวตนในห้องสนทนาบนอินเทอร์เน็ต - ดารินทร์ สวัสดิ์เสวี (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
To study and analyze the appearing identity, called virtual identity, on the Internet Chat Room. To analyze the motivation and the processes of masquerading and to analyze on how the computerization community supports or encourages the masquerading. The methods employed used in this research were content analysis for the first objective, focus group and in-depth interview for the second objective, and filed observation for the third objective. The research theories based on the self concept, Personality, Motivation and Behavior, Computer-Mediated Communications, Postmodern, and Gender theories as the conceptual framework of the research. The results of the research are: 1) The most of physical virtual identities are male, aging between 18-25, with undergraduated education, single, reside in Bangkok, and being students. On the psychology side, there are 5 categories of identities: Sensitive, Autonomy, Attention Drawing, Power, and Self Identify. Yet, by using the self concept and self disclosure, the most founded identities are hidden self (open to self, hidden from others). These identities come to join this virtual community to express their hidden emotion and feeling that they cannot do in the real world because of society s norm and rule. Another founded identity is unknown self who come to find their real self. 2) The reasons of masquerading can be determined by both the physical and psychological needs such as sex, power, love, and so on in which these needs resulting in the motivation and drive that create the masquerading to meet and achieve those needs. 3) The cyberspace environment facilitates and fascinates the masquerading and its processes due to its features of Reduce Sensation, Disinhibition Effect, Flexible Identity, and Alter Perception.